Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)\(pt\Leftrightarrow\frac{1-cos8x}{2}+\frac{1-cos6x}{2}=\frac{1-cos4x}{2}+\frac{1-cos2x}{2}\)
\(\Leftrightarrow cos2x+cos4x=cos6x+cos8x\)
\(\Leftrightarrow2cos3x\cdot cosx=2cos7x\cdot cosx\)
\(\Leftrightarrow2cos\left(cos3x-cos7x\right)=0\)
\(\Leftrightarrow2cosx\cdot\left(-2\right)\cdot sin5x\cdot sin\left(-2x\right)=0\)
\(\Leftrightarrow cosx\cdot sin2x\cdot sin5x=0\)
\(\Leftrightarrow sin2x\cdot sin5x=0\)(do sin2x=0 <=>2sinx*cosx=0 gồm th cosx=0 r`)
\(\Leftrightarrow\left[\begin{array}{nghiempt}sin2x=0\\sin5x=0\end{array}\right.\)\(\Rightarrow\left[\begin{array}{nghiempt}x=\frac{k\pi}{2}\\x=\frac{k\pi}{5}\end{array}\right.\)\(\left(k\in Z\right)\)
b)\(pt\Leftrightarrow1-cos2x+1-cos4x=1+cos6x+1+cos8x\)
\(\Leftrightarrow cos2x+cos8x+cos4x+cos6x=0\)
\(\Leftrightarrow cos10x\cdot cos6x+cos10x\cdot cos2x=0\)
\(\Leftrightarrow cos10x\left(cos6x+cos2x\right)=0\)
\(\Leftrightarrow cos10x\cdot cos8x\cdot cos4x=0\)
\(\Leftrightarrow\left[\begin{array}{nghiempt}cos10x=0\\cos8x=0\\cos4x=0\end{array}\right.\)
\(\Leftrightarrow\left[\begin{array}{nghiempt}x=\frac{\pi}{20}+\frac{k\pi}{10}\\x=\frac{\pi}{16}+\frac{k\pi}{8}\\x=\frac{\pi}{8}+\frac{k\pi}{4}\end{array}\right.\)
\(\Leftrightarrow\frac{1}{2}-\frac{1}{2}cos2x+\frac{1}{2}-\frac{1}{2}cos6x=\frac{1}{2}+\frac{1}{2}cos4x+\frac{1}{2}+\frac{1}{2}cos8x\)
\(\Leftrightarrow cos8x+cos2x+cos6x+cos4x=0\)
\(\Leftrightarrow2cos5x.cos3x+2cos5x.cosx=0\)
\(\Leftrightarrow cos5x\left(cos3x+cosx\right)=0\)
\(\Leftrightarrow2cos5x.cos2x.cosx=0\)
\(\Leftrightarrow\left[{}\begin{matrix}cos5x=0\\cos2x=0\\cosx=0\end{matrix}\right.\) \(\Leftrightarrow\left[{}\begin{matrix}x=\frac{\pi}{10}+\frac{k\pi}{5}\\x=\frac{\pi}{4}+\frac{k\pi}{2}\\x=\frac{\pi}{2}+k\pi\end{matrix}\right.\)
1.
\(\Leftrightarrow\left(1-cos6x\right)cos2x+1-cos2x=0\)
\(\Leftrightarrow cos2x-cos2x.cos6x+1-cos2x=0\)
\(\Leftrightarrow\frac{1}{2}\left(cos8x-cos4x\right)-1=0\)
\(\Leftrightarrow2cos^24x-cos4x-3=0\)
\(\Leftrightarrow\left[{}\begin{matrix}cos4x=-1\\cos4x=\frac{3}{2}\left(l\right)\end{matrix}\right.\)
\(\Leftrightarrow4x=\pi+k2\pi\)
\(\Leftrightarrow x=\frac{\pi}{4}+\frac{k\pi}{2}\)
3.
Đặt \(\frac{x}{6}=t\Rightarrow\frac{1}{4}+cos^22t=\frac{1}{2}sin^23t\)
\(\Leftrightarrow1+4cos^22t=1-cos6t\)
\(\Leftrightarrow cos6t+4cos^22t=0\)
\(\Leftrightarrow4cos^32t+4cos^22t-3cos2t=0\)
\(\Leftrightarrow cos2t\left(4cos^22t+4cos2t-3\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}cos2t=0\\cos2t=\frac{1}{2}\\cos2t=-\frac{3}{2}\left(l\right)\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}t=\frac{\pi}{4}+\frac{k\pi}{2}\\t=\pm\frac{\pi}{6}+k\pi\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}\frac{x}{3}=\frac{\pi}{4}+\frac{k\pi}{2}\\\frac{x}{3}=\frac{\pi}{6}+k\pi\\\frac{x}{3}=-\frac{\pi}{6}+k\pi\end{matrix}\right.\)
\(\Leftrightarrow x=...\)
e/
\(\Leftrightarrow3\left(1-cos6x\right)-\left(2cos^26x-1\right)=4\)
\(\Leftrightarrow-2cos^26x-3cos6x=0\)
\(\Leftrightarrow cos6x\left(2cos6x+3\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}cos6x=0\\cos6x=-\frac{3}{2}\left(l\right)\end{matrix}\right.\)
\(\Rightarrow6x=\frac{\pi}{2}+k2\pi\)
\(\Rightarrow x=\frac{\pi}{12}+\frac{k\pi}{3}\)
d/
\(\Leftrightarrow3\left(1-cos2x\right)-2\left(1-cos^22x\right)=5\)
\(\Leftrightarrow2cos^22x-3cos2x-4=0\)
\(\Leftrightarrow\left[{}\begin{matrix}cos2x=\frac{3+\sqrt{41}}{4}\left(l\right)\\cos2x=\frac{3-\sqrt{41}}{4}\end{matrix}\right.\)
\(\Rightarrow x=\pm\frac{1}{2}arccos\left(\frac{3-\sqrt{41}}{4}\right)+k\pi\)
Nghiệm xấu quá :(
\(sin^2x=cos^22x+cos^33x\)
\(\Leftrightarrow1-cos^2x=2cos^2x-1+4cos^3x-3cosx\)
\(\Leftrightarrow4cos^3x+3cos^2x-3cosx-2=0\)
\(\Leftrightarrow\left(cosx+1\right)\left(4cos^2-cosx-2\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}cosx=-1\\cosx=\frac{1\pm\sqrt{33}}{8}\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=\pi+k2\pi\\x=\pm arccos\left(\frac{1\pm\sqrt{33}}{8}\right)+k2\pi\end{cases}}\left(k\inℤ\right)\)